Visualizing the Poetry of a Statius : An Intertextual Approach - Chinn, Christopher, (Mnemosyne, Supplements ;, 2022)
Scholars have long noted the strikingly visual aspects of Statius' poetry. This book advances our understanding of how these visual aspects work through intertextual analysis. In the Thebaid , for instance, Statius repeatedly presents "visual narratives" in the form of linked descriptive (or ekphrastic) passages. These narratives are subject to multiple forms visual interpretation inflected by the intertextual background. Similarly, the Achilleid activates particularly Roman conceptions of masculinity through repeated evocations of Achilles' blush. The Silvae offer a diversity of modes of viewing that evoke Roman conceptions of gender and class.